What about ICT on Portuguese Language National Syllabi for Mother Tongue Education - Guerra, J. (KSU Publ., 2016)
This paper aims to analyze the references in the Portuguese syllabi for the mother tongue education about the use of information and communication technologies (ICT). We will also characterize the actual students, and their learning nomad methods due to the expansion of Personal Digital Devices (PDD). The author identified gaps between the syllabi and best possible use of ICT in education, namely the creation of a model of the educational process, which would allow to discover and develop the creative potential of students, as noted for the high degree of interactivity and communication technologies to create a unique educational and informative environment that it can be used for a variety of teaching tasks for the study of native and foreign language.
Португал тілін дамытудың ұлттық бағдарламасы негізінде ана тілін оқытуда ақпараттық-коммуникациялық технологияларды қолдану мəселелері
К вопросу использования ИКТ в обучении родному языку в рамках национальной программы функционирования португальского языка
Keywords: ICT in education; educational technologies; mother tongue education; L1 syllabi; ICT practices in syllabus; Portuguese language; mobile learning; Technological Plan of Education; online activities; personal learning environment